Impact of the COVID-19 pandemic on business-to-business relationships in digital ecosystems: an African perspective. Issue 8 (20th January 2023) - Antai, Imoh; Eze, Nonyelum Lina
Abstract : Purpose: In the African context, the threat of the disruption of traditional business value-creation processes, currently facilitated by the growing information technology (IT) ecosystem, came with the coronavirus disease 2019 (COVID-19) pandemic. Thus, this paper aims to investigate the impacts of the COVID-19 pandemic on interfirm relationships within the context of the digital ecosystem in Africa. Design/methodology/approach: This study employs an explanatory–exploratory qualitative approach from an interpretivist stance to investigate the impacts of the COVID-19 pandemic on interfirm relationships. The authors conducted seven in-depth interviews with top management executives in a Nigerian technology company, together with the company's archival data that provided the pre, during and post pandemic (2018–2021) business-to-business (B2B) relationship structures, to determine how these relationships have been affected. Findings: The results suggest that the pandemic had a minimal effect on partnership relationships in the B2B ecosystems of the case company but affected only non-partnership relationships. Research limitations/implications: The authors' qualitative study is interpretive and the sample size is limited. Hence, there is a need for caution in generalizing the findings. The framework can be further validated across a wider population. Practical implications: Partnerships can help organizations weather business crises. Consequently, organizations should maintain a healthy number of partnership relations to deal with periods in which challenges emerge in the business landscape. In other words, with tight contracts and a strategic focus on goals and objectives, partnership relations can help organizations weather business crises. Originality/value: This study builds upon the burgeoning body of literature on digital ecosystems within the African context, which is a relevant contextual contribution.